Engagement in Ecosystems : Duality and Interplay of Actors' roles - Vuorinen, Tiia Maria Tuulia (My University, 2023)
In marketing literature, the popularity of the concept of engagement has been skyrocketing in recent years. However, despite of the widespread interest in engagement among researchers, no mutual consensus has been achieved in conceptualising engagement. The phenomenon has been examined from various perspectives, such as actor engagement, collective engagement, customer, or consumer engagement. In addition, engagement has been conceptualised for example as a behavioural phenomenon but also as a disposition, which brings duality to the concept of engagement. This study’s aim is to find out, how the engagement forms or is created in a heterogenous ecosystem. This aim is approached with three research questions. This study uses the instrumental case study as a research strategy to examine the engagement as a phenomenon through the case ecosystem, and thus the aim is to produce theoretical information that will be applicable to other contexts as well. The case ecosystem is an example of an ecosystem consisting of heterogenous actors, which is why the case ecosystem was chosen for examination. The empirical data has been collected with group interviews and one-to-one interviews of the central actors of the ecosystem, but also by going native in the case ecosystem, as the researcher has been an integral part of the case ecosystem as a project worker in a project team. The study examines engagement through psychological, emotional, and behavioural dimensions, which separates this study from many others, that address engagement either unidimensionally or use only two of these dimensions in reviewing engagement. The most important findings of this study are the engagement activities, which are bound to the engagement dimensions, the outcomes of these engagement activities, the different levels of engagement, and finally the inseparability and interchangeability of being either a subject or an object of engagement. The terms engager and engagee are introduced as well to describe the interchanging roles of actors. The result of this study is the empirically enriched framework, which builds on the theoretical framework.
Keywords: roles (expected behaviour); engagement (properties); ecosystem services; committing oneself; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|